The Nosological Structure of Eye’s Diseases in Workers with Harmful Working Condition. Review - A. V. Aksyonenko; E. V. Gromakina (Oftalʹmologiâ, 2022)
The organ of vision is one of the target organs, which is negatively influenced by a number of harmful factors of the working environment and the labor process. Under their influence, the functioning of the visual analyzer can be disrupted, the risk of developing various diseases and injuries increases. The problem of the ophthalmopathology development in persons employed in hazardous industries is relevant, since the protection of the health of the working-age population is of great socio-economic importance. The proposed review of the literature presents the structure and frequency of occurrence of ophthalmopathology in workers of the cement industry, oil refining and petrochemical industries, metallurgical industry, coal and mining industries, manganese ore industry, synthetic rubber production, rubber technical products, synthetic ethyl alcohol, bakery, aviation production, also workers of the underground and railways of the main professions, including those who service underground tunnels. The data of the nosological structure of ophthalmopathology of various hazardous industries workers in Ukraine, India, and some African countries are presented. Among the professionally conditioned pathology of the vision organ, diseases of the anterior part of the eyeball are most common: chronic conjunctivitis, blepharitis, blepharoconjunctivitis, dry eye syndrome. In the general diseases’s structure of the vision organ, the first place is occupied by anomalies of refraction (from 14.3 to 88.9 %). The share of eye injuries ranges from 4 to 12.5 %. The frequency of occurrence of various ophthalmopathologies increases among workers with more than 10–15 years professional experience, which is typical for all industries and industries; there is also a direct connection between diseases of the organ of vision and the class of harmfulness of working conditions.